Modular instruction on population education for fast learners (intermediate grades) - Gonzales, Lolita C. 1944-; Adorio, Mercedes P. (Quezon City College of Education, University of the Philippines Diliman, 1975)
The study is an attempt to teach population education in a more extensive and individualized manner in order to cater to the needs of fast learners. Modules were presented through research-oriented instructional procedures. The concepts included are within the scope of the population education curriculum for the intermediate grades as prepared by the Bureau of Public Schools. Enrichment activities and the introduction of research methods and techniques such as survey, interview, observational study and experimentation were included. Moreover, debating and statistical processes like the measures of central tendency, range and the normal curve were incorporated to challenge the fast learning children.
Vita.
Thesis (Master of Arts in Teaching Special education - Giftedness)--University of the Philippines, Diliman
Keywords: Population -- Study and teaching (Elementary) -- Philippines